2023
DOI: 10.1371/journal.pone.0283582
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of the rural community about cutaneous leishmaniasis in Wolaita zone, southern Ethiopia

Abstract: Background Cutaneous leishmaniasis (CL) is a neglected tropical disease that is caused by a Leishmania parasite and transmitted by the bite of infected female sandflies. Community awareness is an essential component of disease control and prevention. Therefore, this study aimed to assess the community’s knowledge, attitude, and practice toward CL in Wolaita zone, southern Ethiopia. Methods A community-based cross-sectional study design was employed to include 422 study subjects selected using a systematic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
5
4
0
Order By: Relevance
“…Importantly, most did not know how it is transmitted and that it can be treated. This is in line with findings from other studies, where patients or individuals living in endemic areas know about the disease, but little about its transmission and treatments [2528]. Better knowledge about how the disease is transmitted and the use of bed nets are likely to reduce CL transmission by sand flies.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, most did not know how it is transmitted and that it can be treated. This is in line with findings from other studies, where patients or individuals living in endemic areas know about the disease, but little about its transmission and treatments [2528]. Better knowledge about how the disease is transmitted and the use of bed nets are likely to reduce CL transmission by sand flies.…”
Section: Discussionsupporting
confidence: 88%
“…In comparison with KAP surveys conducted in CL-endemic areas in other countries, a previous study in rural communities of southern Ethiopia found that all heads of households studied did not know the mode of CL transmission and had never heard of sandflies, with only 19% (80/422) having a good level of CL-related knowledge 18 . Similarly, very poor levels of knowledge about the disease and its vector were reported in endemic areas of Kerala, India 19 and Khyber Pakhtunkhwa, Pakistan 14 .…”
Section: Discussionmentioning
confidence: 68%
“…For descriptive data, frequency, percentage, and mean (standard deviation) or median (interquartile range) were used, where applicable, to describe the KAP components and independent variables. Scores were developed for the participants’ responses on questionnaire items related to knowledge, attitude and practices following the methods described previously 18 , 27 . In brief, from the KAP questionnaire, a composite score of each component was calculated for each participant where each correct response received a score of 1 and each incorrect or unsure response received a score of 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt-related health knowledge was assessed in part 2 by 6 categorical questions about the WHO-recommended maximum daily salt consumption level [ 4 ], long-term health issues associated with a high-salt diet, diagnostic criteria for hypertension, and causes, complications and preventive strategies for hypertension. One point was awarded to each correct answer [ 37 ]. This section had a maximum score of 6 points.…”
Section: Methodsmentioning
confidence: 99%